Clinical mentorship for specialized care. Training paradigms and emerging challenges of assessment - Graciela Gonzalez Juarez (Archives of Nursing Practice and Care - Peertechz Publications, 2022)
Introduction: The following research is developed within the framework of the Project 135 of the National School of Nursery and Obstetrics (ENEO), with the contribution of the GIIIDEE Group (Interdisciplinary Group of Innovation and Research of Educational Assessment in Nursery). The global context had many significant changes starting 2019, since the emergence of COVID-19, a phenomenon that had significant repercussions on the training and assessment of the clinical skills in real scenarios with important implications for internships in students of higher education, both undergraduate and postgraduate. Theoretical framework: The theoretical referent is the Model of Reflexive Mentorship for Nursery. The clinical tutor is a professional specialist in nursery in charge of the clinical training of his/her students in real scenarios, in order to develop their critical thought, clinical judgment and decision making in the clinical field or community insert, both in metropolitan and foreign headquarters.  Objective: The main goal of this document is to identify the training challenges and the assessment of the clinical mentorship for the tutors specialized in mentorships, orientations and guides in the clinical practices that take place in real contexts at different locations of the Unique Program of Nursery Specialties (PUEE). The methodology consisted on a bibliographical research in order to realize the state of art. The results show four important challenges for clinical mentorship at PUEE in the post-pandemic stage. The theoretical and methodological challenges are diverse in order to provide the mentorship as a unified policy with the commented perspectives that appear in the document. The teaching in situ and the formative assessment can potentiate the didactics in mentorship and the development of professional skills.